Municipal solid waste incineration fly ash as activator for ground granulated blast-furnace slag: Hydration behavior and stabilization/solidification effectiveness - Haijie He; Yufei Gao; Jing Yu; Wenjie Zhang; Xinyu Shen; Maoyu Zhang (Case Studies in Construction Materials)
Portland cement is conventionally used for stabilization/solidification (S/S) treatment on municipal solid waste (MSW) incineration fly ash (IFA). However, its relatively low S/S efficiency leads to excessive volume/mass and unsatisfaction to the requirements for landfilling with common MSW. In this work, ground granulated blast-furnace slag was used for S/S treatment on the IFA. Hydration behavior, mechanical strength and immobilizing effectiveness on heavy metals, chlorine and sulfur of IFA-slag paste were systematically investigated and compared to those of IFA-cement paste. Results indicated that the IFA provided sufficient alkali to activate slag hydration. When mixed at 50:50, similar hydration products were observed for both types of pastes, although less ettringite and more Friedel’s salt were found in the IFA-slag paste. More C-(A)-S-H in higher polymerization was also found in the IFA-slag paste, contributing to pore refinement and higher compressive strength. Increasing the slag content accelerated hydration of the IFA-slag paste, forming more hydration products that further refined the pore structure. A 28-day compressive strength as high as 43 MPa was achieved when the IFA and slag were blended at 25:75. Furthermore, slag had higher efficiency over cement in transforming the heavy metals in the IFA to more stable speciation. Considering the leachability of heavy metals, the IFA content in the mixture could be increased while still complying with the requirements for landfilling with common MSW. Sulfur was more effectively immobilized than chlorine, due to the preferential precipitation of ettringite over Friedel’s salt.